2018
DOI: 10.3130/jaabe.17.133
|View full text |Cite
|
Sign up to set email alerts
|

The Socioeconomic Characteristics, Urban Built Environment and Household Car Ownership in a Rapidly Growing City: Evidence from Zhongshan, China

Abstract: Growth in car ownership has significant impacts on the use of urban space and management of urban environments, especially in rapidly developing countries such as China. However, among voluminous literature, few studies have investigated the correlates of household car ownership in the Chinese context, leading to the lack of effective measures to tackle rapid motorization. This study explored the impacts of household-level socioeconomic characteristics and neighborhood-level built environment on household car … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…As confirmed in this study, high density neighbourhoods offer access to a large number of food and retail outlets [46], which are the primary motivators of utilitarian walking trips within the neighbourhood [5]. This study also supports the hypothesis that, via the provision of food/retail destinations and an interconnected street network, densification reduces car dependency [47] resulting in more active utilitarian trips and higher amounts of transportation walking in the local community [48].…”
Section: Transportation Walkingsupporting
confidence: 83%
See 1 more Smart Citation
“…As confirmed in this study, high density neighbourhoods offer access to a large number of food and retail outlets [46], which are the primary motivators of utilitarian walking trips within the neighbourhood [5]. This study also supports the hypothesis that, via the provision of food/retail destinations and an interconnected street network, densification reduces car dependency [47] resulting in more active utilitarian trips and higher amounts of transportation walking in the local community [48].…”
Section: Transportation Walkingsupporting
confidence: 83%
“…1) [46]. Higher residential, public transport and destination densities were expected to result in less green space (park area) [44] and household car ownership to be more prevalent among respondents living in areas with lower residential, street intersection, food/retail, recreation and public transport densities [47]. Frequency of within-neighbourhood transportation walking was expected to be negatively related to household car ownership [48] and positively associated with street intersection and destination densities [5].…”
Section: Mediated and Direct Effects Of Urban Densification On Walkingmentioning
confidence: 99%
“…Unpublished data from a previous study conducted in Hong Kong suggested that these relationships might be curvilinear (inverted-U or concave down, increasing). Household car ownership was expected to be more prevalent among respondents living in areas with lower residential, commercial/civic destination, recreation and public transport densities [53]. We hypothesised that MVPA would be unrelated to residential density [9,12] and positively associated with commercial and civic destinations, recreation facilities, public transport stops and number of parks [9].…”
Section: Total Effects Of Neighbourhood Environmental Attributes On Mmentioning
confidence: 97%
“…Based on the existing literature, the research of vehicle ownership and vehicle type is not sufficient in China. Firstly, most studies in China mainly analyze the vehicle ownership of a single type [36][37][38], rather than discussing the correlation and transition of vehicle ownership between different types. Secondly, the ownership of electric bicycle is seldom considered in model framework [39,40].…”
Section: Introductionmentioning
confidence: 99%